2003
DOI: 10.1172/jci200318921
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: a critical update

Abstract: IntroductionIn the mid 1990s, immunoassays for C-reactive protein (CRP), with greater sensitivity than those previously in routine use, revealed that increased CRP values, even within the range previously considered normal, strongly predict future coronary events. These findings triggered widespread interest, especially, remarkably, in the US, where the clinical use of CRP measurement had been largely ignored for about 30 years. CRP production is part of the nonspecific acute-phase response to most forms of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
796
3
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,064 publications
(830 citation statements)
references
References 57 publications
20
796
3
11
Order By: Relevance
“…Our data demonstrate a robust and sexually dimorphic up‐regulation of pentraxin 2/APCS, the functional murine equivalent of C‐reactive protein in human. C‐reactive protein and APCS are induced in response to a variety of inflammatory stimuli primarily via IL‐6, serving a key role in acute‐phase responses 27, 28. We also found that KPC increases hepatic expression of Orm1 , another key acute‐phase reactant in both mouse and human known to serve numerous important roles in energy balance, immunity, and capillary barrier modulation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our data demonstrate a robust and sexually dimorphic up‐regulation of pentraxin 2/APCS, the functional murine equivalent of C‐reactive protein in human. C‐reactive protein and APCS are induced in response to a variety of inflammatory stimuli primarily via IL‐6, serving a key role in acute‐phase responses 27, 28. We also found that KPC increases hepatic expression of Orm1 , another key acute‐phase reactant in both mouse and human known to serve numerous important roles in energy balance, immunity, and capillary barrier modulation.…”
Section: Discussionmentioning
confidence: 57%
“…We specifically examined the acute‐phase proteins pentraxin 2/APCS, which in mice serves an analogous role to C‐reactive protein in humans, and Orm1, which has recently been shown to have anorexigenic properties 18, 27, 28. In males, KPC induced a 34.42 ± 6.89‐fold increase in Apcs ( P  < 0.001, n  = 4–5 per group) and a 6.61 ± 0.32‐fold increase in Orm1 relative to controls ( P  < 0.001, n  = 4–5 per group) ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…hs-CRP circulates freely in the plasma because there are no specific transporters for it 1,2. It has been shown that hs-CRP is a powerful predictor of cardiovascular adverse events and mortality in unstable coronary heart disease 3-5.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a blood plasma protein that is indicative of inflammation and infection and a risk predictor of cardiovascular disease. It is considered an indicator of bacterial infection, pneumonia, and tissue damage (Pepys & Hirschfield, 2003; Pearson et al, 2003; Simon, Gauvin, Amre, Saint‐Louis, & Lacroix, 2004; Tillett & Francis, 1930). The median of CRP in our sample is 1.7 mg/L, but its distribution is highly skewed.…”
Section: Methodsmentioning
confidence: 99%
“…The value rises within few hours of disease onset. Inflammation and bacterial infection can produce a rise in CRP values up to 1,000‐fold (Gruys, Toussaint, Niewold, & Koopmans, 2005; Pepys & Hirschfield, 2003). Fibrinogen is a coagulation protein produced by the liver that helps the body in the formation of blood clots.…”
Section: Methodsmentioning
confidence: 99%